Phytochemical analysis of eight Genista L. taxa (Fabaceae) from natural populations in Bosnia and Herzegovina - Pustahija, Fatima; Bašić, Neđad; Starčević, Mirsada; Subašić, Mirel; Boškailo, Aldin; Parić, Adisa; Hukić, Emira (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2023)
Phytochemical analysis of aerial parts of eight autochthonous Genista L. taxa (brooms; Fabaceae; G. germanica, G. januensis, G. pilosa, G. radiata, G. sagittalis, G. sericea, G. sylvestris ssp. dalmatica and G. tinctoria) from natural populations in Bosnia and Herzegovina was performed in this study. Using fast phytochemical methods, for the first time, emodin was identified in the genus; coumarins, fatty acids, saponins, steroids, tannins and terpenoids in some taxa, but also the presence of phenolic compounds or the absence of anthocyanins in all studied taxa. The analysis of total phenol (TPC), flavonoid (TFC), phenolic acids (TPA) and alkaloid (TA) contents and antioxidant activity (DPPH), determined by spectrophotometry method, indicated the existence of differences between the studied taxa (p<0.01). The taxa differed significantly from each other in TPA and TA, and the least in terms of antioxidant activity. There is a positive correlation between TPA, TPC and TFC in one hand, and TA and antioxidative activity in other (p<0.01). The Euclidean dendrogram indicates two main clusters: the first cluster includes G. januensis and G. pilosa, and the second is derived from the remaining six taxa. Obtained PCA clusters were more diffused than those generated by Euclidean distance dendrogram but in a good agreement with them. The obtained data indicate the need for further phytochemical and pharmacological research of the genus Genista, as a very interesting source of natural active compounds, as well as population research with special emphasis on the influence of microclimate on SMs content.